Conflicts in Ethiopia since the 17th century: Scales and discourses - Ramos, M. (State and Societal Challenges in the Horn of Africa, 2013)
Conflicts in Ethiopia since the 17th century: Scales and discourses presents some of the root causes for the recent intra and inter-religious conflicts occuring in present day Ethiopia.